2022
DOI: 10.1002/ajmg.c.32025
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological features in RASopathies: A pilot study on parent training program involving families of children with Noonan syndrome

Abstract: Noonan syndrome (NS) is a clinical variable multisystem disorder caused by mutations in genes encoding proteins involved in the RAS/mitogen-activated protein kinase signaling pathway. NS is characterized by a distinctive facies, short stature, and congenital heart defects. Psychomotor delay, learning difficulties, and social deficits are also common. Furthermore, behavioral and attention problems can be reckoned as a key symptom in NS, with functioning resembling the patterns observed in attention deficit hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…been described in children with Noonan syndrome -one of the most common, (~1:1500, (Jindal et al, 2015), prevalence sex-balanced), and best documented RASopathies -and initial results suggest that ADHD-like parental training programmes might have similarly positive therapeutic effects on Noonan patients (Montanaro et al, 2022). A recent structural brain imaging study in such children and controls revealed RASopathy-related changes in striatal and cortical anatomy, possibly affecting inhibition functions via frontostriatal circuits, similar to observations in ADHD (Rai et al, 2023).…”
Section: Rasopathiesmentioning
confidence: 99%
“…been described in children with Noonan syndrome -one of the most common, (~1:1500, (Jindal et al, 2015), prevalence sex-balanced), and best documented RASopathies -and initial results suggest that ADHD-like parental training programmes might have similarly positive therapeutic effects on Noonan patients (Montanaro et al, 2022). A recent structural brain imaging study in such children and controls revealed RASopathy-related changes in striatal and cortical anatomy, possibly affecting inhibition functions via frontostriatal circuits, similar to observations in ADHD (Rai et al, 2023).…”
Section: Rasopathiesmentioning
confidence: 99%